Antifungal Activity of Propolis Against Postharvest Disease Agent Penicillium digitatum - Soylu, E.M.; Özdemir, A.E.; Ertürk, E.; Sahinler, N.; Soylu, S. (Asian Journal of Chemistry, 2010)
The in vitro and in vivo antifungal activity of the propolis was evaluated against fungal pathogen Penicillium digitatum, causal agent of green mold of citrus fruits. The germination of conidia completely inhibited by 10, 50 and 100 μg mL-1 concentrations of propolis extracted in 70 % ethanol. The same concentrations of propolis extracted in 35 % ethanol also inhibited conidial germination by 31, 68 and 93 % respectively. The in vivo effect of propolis on the spoilage of Star Ruby grapefruits by Penicillium was also evaluated at room temperature. None of the concentrations of propolis extracted in 70 % ethanol prevented the fungal growth on artificially inoculated fruits. The 100 μg mL-1 propolis extracted in 70 % ethanol, however, provided complete inhibition of naturally occurring green mold disease on wounded but uninoculated control fruits.